Meconium aspiration syndrome: do we know? - Yurdakök, Murat (The Turkish Journal of Pediatrics, 2011)
Meconium is a common finding in amniotic fluid and placental specimens, particularly in the term or post-term pregnancy. The most important consequence of meconium-stained amniotic fluid (MSAF) is meconium aspiration syndrome (MAS), and at least 5% of infants born through MSAF develop MAS. MAS continues to be a threat to many newborns throughout the world, with a case fatality rate of 5% (as much as 40%), in addition to short- and long-term pulmonary and neurodevelopmental sequelae. The exact pathophysiology of meconium passage into the amniotic fluid and consequences of meconium aspiration are unknown. There are three prevailing and possibly compatible theories for mechanisms of meconium release. Firstly, meconium passage is probably related with the maturation of the gastrointestinal tract, because meconium passage in the preterm third trimester fetus has been reported to be a rare event, as typically it occurs near or post-term. Secondly, an alternate hypothesis for in utero meconium passage is that pathologic processes, such as stress via hypoxia or infection, can trigger meconium passage. However, the predictive values of MSAF for fetal distress and acidosis at birth are poor and controversial. Thirdly, an alternative route for the presence of MSAF in the presence of fetal hypoxia is reduced clearance of defecated meconium due to impaired fetal swallowing or unidentified placental dysfunction in addition to or instead of an increase in its passage. The pathophysiology of MAS is multifactorial and extremely complex. Meconium causes mechanical obstruction and pulmonary air leak, induces surfactant inactivation, causes pulmonary inflammation, and induces apoptosis. Preventing prolonged pregnancy by labor induction might reduce the risk of MSAF. Labor induction with prostaglandins appears to be associated with the occurrence of MSAF. Amnioinfusion for suspected umbilical cord compression has no clear effect on the occurrence of MSAF. Intrapartum suctioning of the naso- and oropharynx before delivery of the shoulders as well as postnatal endotracheal suctioning of vigorous infants with MSAF are no longer recommended. Currently, endotracheal suction is recommended only in neonates born through MSAF who are not vigorous at birth. Indications for mechanical ventilation in infants with MAS are arbitrary. Surfactant administration may reduce the severity of MAS. Bronchoalveolar lavage with surfactant in infants with MAS is risky and it cannot be recommended for routine use. At present, there is insufficient evidence to propose routine steroid therapy in the management of MAS. Although prophylactic antibiotics in infants with MAS are not justified, most of these patients receive antibiotics during the first days of life, before the diagnosis of pneumonia can be completely ruled out. Children surviving severe MAS are in fact reported to have higher prevalence of asthmatic symptoms and bronchiolar hyperreactivity than children in the general population. It remains undetermined how often and at what intensity systemic inflammation occurs in association with MAS and what its significance is for the outcome of infants with severe MAS.